Pengembangan Potensi Kepemimpinan Transformasional Dalam Pendidikan Islam - M. Nafiur Rofiq (FALASIFA : Jurnal Studi Keislaman, 2020)
Transformational leadership in Islamic education will always make Islamic values in its leadership. Communication between superiors and subordinates is not just in the realm of organization, but in Islam there is fostering relations between human beings. Leadership education are expected to be able to make corrections to the behavior that exists in the organization, and leaders of an institution are able to implement quality standards. Quality improvement and management development are very much considered. Individuals as leaders of their existence are responsible for Islamic education institutions, leadership development (leadership development) of its existence can be interpreted as an extension of one's capacity to run a management to achieve something more effective in leadership roles and processes.